Noncoding RNA of Glutamine Synthetase I Modulates Antibiotic Production in Streptomyces coelicolor A3(2) - D'Alia, Davide (American Society for Microbiology (ASM), 2010)
Overexpression of antisense chromosomal cis-encoded noncoding RNAss (ncRNAs) in glutamine synthetase I resulted in a decrease in growth, protein synthesis, and antibiotic production in Streptomyces coelicolor. In addition, we predicted 3,597 cis-encoded ncRNAs and validated 13 of them experimentally, including several ncRNAs that are differentially expressed in bacterial hormone-defective mutants.